Mediating Sustainable Regional Development: The Role of Indonesia’s Supreme Audit Institution in Economic Growth and Fiscal Governance - Sastra, Cipta Dwi; Lubis, Satia Negara; ., Badaruddin; Thoha, Achmad Siddiq (Journal of Cultural Analysis and Social Change, 2026)
This study examines whether and how Indonesia’s Supreme Audit Institution (BPK) mediates the relationships between economic growth, local revenue, investment, and sustainable regional development (SRD) across 33 districts/municipalities in North Sumatra. Using a quantitative, explanatory design with PLS-SEM, we integrate survey responses from 539 local officials (finance offices, inspectorates, and strategic agencies) with administrative indicators. SRD is modelled as a second-order reflective construct (economic–social–environmental), while BPK is treated as a governance mediator operating through findings and follow-up (TLRHP). Results show a large, precisely estimated positive direct association between growth and SRD (β = 0.709, p < .001). Growth (β = 0.280, p = .001) and local revenue (β = 0.294, p < .001) are both positively associated with audit intensity, yet the same-year association between BPK and SRD is negative (β = −0.261, p = .008), yielding negative derived indirect effects via BPK for growth (−0.073) and revenue (−0.077). Investment has no significant direct effect on SRD (p = .243) and only a modest link to BPK (β = 0.134, p = .036), producing a small negative indirect effect (−0.035). The pattern is consistent with problem-triggered, corrective audits: oversight intensifies where outcomes lag, so contemporaneous correlations are negative and benefits emerge with a policy-cycle lag (t+1) once findings are closed and integrated into RKPD/APBD. Policy implications include institutionalizing audit-to-budget linkages (TLRHP→RKPD/APBD-P), adopting lag-aware performance indicators, and targeting high-elasticity investments (connectivity, basic services) to convert fiscal capacity into sustainable development outcomes.